The changing landscape of China's consumerism - Hulme, Alison (Chandos Asian studies series., 2014)
Consumerism in China has developed rapidly. The Changing Landscape of China's Consumerism looks at the growth of consumerism in China from both a socio-economic and a political/cultural angle. It examines changing trends in consumption in China as well as the impact of these trends on society, and the politics and culture surrounding them. It examines the ways in which, despite needing to 'unlock' the spending power of the rural provinces, the Chinese authorities are also keen to maintain certain attitudes towards the Communist Party and socialism 'with Chinese Characteristics'. Overall, it ai.